Transferable utility and demand functions - Pierre-André Chiappori; Elisabeth Gugl (Theoretical Economics, 2020)
While many theoretical works, particularly in Family Economics, rely on the Transferable Utility (TU) assumption, its exact implications in terms of individual preferences have never been fully worked out. In this paper, we provide a set of necessary and sufficient conditions for a group to satisfy the TU property. We express these conditions in terms of both individual indirect utilities and individual demand functions. Lastly, we describe the link between this question and a standard problem in consumer theory (initially raised by Gorman 1953), and explain why a similar characterization in terms of direct utilities cannot obtain.
Keywords: D1; C7; 330; Transferable utility; matching; Gorman polar form